The status, problems and development trend of China's industrial hemp - Guangwen Wu; liguo Zhang; Yuyan Fang; Nan Zheng; Ming Zhang; Xixia Song; Hongmei Yuan; Lili Cheng; Si Chen (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
This article reviews the historical evolution, current status, existing problems and development trend of China's industrial hemp industry. The paper plays a role in promoting the healthy and sustainable development of China's industrial hemp industry.